Personal Branding Kreator Gen Z dalam Membentuk Literasi Keuangan di TikTok - Wee, Angeline; Paramita, Sinta; Utami, Budi (Kiwari, 2026)
The development of social media has opened up opportunities for young people, especially Gen Z, to build digital identities and shape audience behavior through creative content. One example of this is seen in content creators on TikTok who develop personal branding to convey financial education. This study aims to determine the personal branding strategies used by Gen Z content creator @jsnnath in shaping a digital identity through financial education content, influencing audience perceptions, and its impact on the development of financial literacy. This study uses the theories of mass self communication, personal branding strategies, and impression management as a foundation. The research method used was a case study with a qualitative approach through interviews, observation, and documentation. The results showed that @jsnnath built a personal brand through consistent delivery of educational content, a simple and easy-to-understand communication style, and the use of strategies such as self-confidence, self-promotion, setting a good example, and humility and collaboration to strengthen the image of competence and humanity. Furthermore, the digital identity was formed through consistent visuals, interactive responses, and an emphasis on educational value that is free from manipulation. This strategy successfully built audience trust and strengthened its position as a reference for financial literacy among Gen Z. Perkembangan media sosial telah membuka peluang bagi generasi muda, khususnya Gen Z, untuk membangun identitas digital sekaligus membentuk perilaku audiens melalui konten kreatif. Salah satu bentuk pemanfaatannya terlihat pada content creator di TikTok yang mengembangkan personal branding untuk menyampaikan edukasi keuangan. Penelitian ini bertujuan untuk mengetahui strategi personal branding yang digunakan oleh content creator Gen Z @jsnnath dalam membentuk identitas digital melalui konten edukasi keuangan, perannya terhadap persepsi audiens, serta kontribusinya dalam membentuk literasi keuangan. Penelitian ini menggunakan landasan teori mass self communication, strategi personal branding, dan impression management. Metode penelitian yang digunakan adalah studi kasus dengan pendekatan kualitatif melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa @jsnnath membangun personal branding melalui konsistensi penyampaian konten edukatif, gaya komunikasi yang sederhana dan relevan, serta penggunaan strategi seperti penghargaan diri, promosi diri, pemberian contoh baik, serta kerendahan hati dan kolaborasi untuk memperkuat citra kompeten sekaligus humanis. Selain itu, identitas digital dibentuk melalui visual yang konsisten, respon interaktif, dan penekanan pada nilai edukatif yang bebas dari manipulasi. Strategi tersebut berhasil membangun kepercayaan audiens serta memperkuat posisinya sebagai rujukan literasi keuangan di kalangan Gen Z.